Contribution to the declination of the dependability requirements using a three-dimensional decomposition of complex systems - S SAADI; M DJEBABRA; W BOULAGOUAS (Prod. Eng. Res. Devel, 2018)
The declination of the dependability requirements of the complex systems is one of the most critical processes of systems conception as well as systems engineering. We consider that these dependability requirements must be globally considered at the complete system level if they are to be respected before being allocated on the components of the system. Our approach is based on a three-dimensional decomposition model of the system whose purpose is to describe the way in which the system operates in order to deduce its dysfunction that serves as a basic support for the declination of the dependability requirements. The proposed method is applied to a nitric acid cooling system before being introduced into a chemical reactor.